2021
DOI: 10.1002/pen.25710
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of porous polydimethylsiloxane structures with adjustable porosity and pore morphology using emulsion templating technique

Abstract: Porous polydimethylsiloxane (PDMS) framework with adjustable pore structures has been fabricated by polymerization of the continuous phase in the emulsion templates. Different types of surfactants, including nonionic (Triton X‐100), cationic (Benzalkonium chloride), anionic (sodium dodecyl sulfate), and silicone‐based block copolymer were used to stabilize the water‐in‐oil emulsion system. Deionized water with a wide range of internal phases varying from 10% to 60% by weight was employed to make the low intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In the meantime, the polydispersity may be of interest for certain applications, as reported in the case of materials with gradient pore size for scaffolds and extracellular matrix [ 34 , 35 ]. Similar size and morphology of the pores and some adjustments in pore distribution by nature and concentration of the surfactants were reported by Abshirini et al [ 36 ], for porous silicones obtained by hydrosilylation in emulsion templating. Even larger pores were reported for porous silicones (sponges or foams) obtained with solid NaCl [ 37 ] or supercritical CO 2 [ 38 ] as templates.…”
Section: Resultssupporting
confidence: 83%
“…In the meantime, the polydispersity may be of interest for certain applications, as reported in the case of materials with gradient pore size for scaffolds and extracellular matrix [ 34 , 35 ]. Similar size and morphology of the pores and some adjustments in pore distribution by nature and concentration of the surfactants were reported by Abshirini et al [ 36 ], for porous silicones obtained by hydrosilylation in emulsion templating. Even larger pores were reported for porous silicones (sponges or foams) obtained with solid NaCl [ 37 ] or supercritical CO 2 [ 38 ] as templates.…”
Section: Resultssupporting
confidence: 83%
“…It indicated that the same mass of deionized water was separated into the micelles with different sizes, when the SDS concentration decreased from 1:20 to 1:80. It means that the internal pore size would increase as the SDS concentration decreased because of the larger micelles [34]. However, the pore size did not increase linearly when the SDS concentration decreased.…”
Section: Optimization Of the Micro-patterned Porous Pdmsmentioning
confidence: 96%
“…The outstanding characteristics of this sensor were mainly benefited from the specific protruding surface micro-structure and the internal pores, according to the previously mentioned. On the one hand, the distance of the two electrodes would decrease dramatically when the sensor suffered from an external force [21,33,34]. On the other hand, the air in the pores would be squeezed out, and the relative permittivity of the whole dielectric layer would increase simultaneously since the much smaller dielectric constant of air than PDMS [7,10,35].…”
Section: Introductionmentioning
confidence: 99%
“…However, existing reports only focused on DNA synthesis on planar PDMS surfaces with low synthesis yield . Several fabricating methods of porous PDMS were reported, such as templating, emulsion, phase separation, , and 3D printing . As porous PDMS possesses a higher surface-to-volume ratio, it can provide a larger area for DNA synthesis and facilitate synthesis yield improvement.…”
Section: Introductionmentioning
confidence: 99%